Livelihood diversity and fishing skill during COVID-19 lockdowns in French Polynesia - Matthew Lauer; Jean Wencélius; Paige Dawson; Sally J. Holbrook; Sarah E. Lester; Scott D. Miller; Shannon Nelson-Maney; Andrew Rassweiler; Russell J. Schmitt (Frontiers in Marine Science)
Small-scale fisheries provide seafood for billions of people and are one of the largest employers in many coastal communities. Those households engaged in these fisheries who maintain diverse income sources are generally thought to be better prepared to cope with social or ecological perturbations such as the crises presented by the COVID-19 pandemic. One outcome of the COVID-19 crisis was the collapse of international tourism after many nations instituted strict border controls to slow the virus’s spread, severely impacting coastal communities that depend on tourism-related employment. This research assessed the effects of COVID-19-induced collapse of tourism on small-scale coral reef fishers and households in Moorea, French Polynesia. Ninety-five households were surveyed about their livelihoods, fishing, demographics, and income-generating occupations before and after the lockdown. Shifts in fish biomass were evaluated using time series data collected through underwater visual surveys, and roadside fish vendors were surveyed to assess fish sales. Results showed that after tourism employment evaporated more Moorea households began fishing to boost their incomes and food security. However, the increase in fishing pressure showed no appreciable decline in the biomass of fishable species. The households responsible for the increased fishing activities were those who were working in the tourism economy prior to the pandemic and subsequently lost their jobs. Households that combined fishing with construction or other stable sectors showed greater abilities to cope, while those combining fishing with tourism were heavily impacted. Importantly, results showed that those households devoted solely to fishing managed the crisis adeptly due to their superior fishing skills and ecological knowledge. This pattern suggests that not all forms of household livelihood diversification confer equal advantages and that resource-dependent households are not necessarily intrinsically less resilient. More generally, it is argued that we should be cautious when promoting livelihood diversification as a blanket solution to decrease household vulnerability, and that ecological knowledge diversity is underappreciated.